Cost-Effectiveness of Treatment for Tobacco Dependence : A Systematic Review of the Evidence - Ronckers, Sandy; Ament, Andre (World Bank, Washington, DC, 2013)
Good decisions on which health interventions to invest can be facilitated by high quality evaluations of the cost-effectiveness of interventions. Although there are several reviews of evaluations of the cost-effectiveness of smoking cessation programs, the reviews have had little to say about the quality of the studies. The present study tries to fill this gap by thoroughly evaluating the quality of economic evaluations of interventions to reduc e tobacco consumption. First, the general characteristics of all the studies reviewed are described, and then the quality of epidemiological characteristics and of the economic evaluation is analyzed, using a criteria list proposed by Drummond et al. (1997). The analysis finds that the quality of many aspects of many of the studies leaves much to be desired, judged against the guidelines offered by Drummond et al. However, the studies do consistently conclude that stop-smoking interventions are cost-effective, and this conclusion is robust when sensitivity analyses are performed. The cost-effectiveness ratios estimated by the studies for smoking cessation interventions are much lower than most other health care treatments. The study this concludes that the broad conclusion that treatments to reduce the number of smokers are cost-effective at least in relative terms, is likely to be true, despite the concerns expressed about the quality of the economic evaluations. The implication for policymakers is that smoking cessation interventions are worthwhile.